Solid‐Supported Materials‐Based Synthesis of 2‐Substituted Benzothiazoles: Recent Developments and Sanguine Future. Issue 25 (1st July 2021) - Singh, Rahul; Sindhu, Jayant; Devi, Meena; Kumar, Ashwani; Kumar, Ramesh; Hussain, Khalid; Kumar, Parvin
Abstract: Benzothiazole and its derivatives have been manifested as an optimistic scaffold due to their immense biological importance. Several methodologies have been reported as modifications after the first report of 2‐substituted benzothiazole. Among them, many involve a shift from the conventional synthetic approach by utilizing different catalytic systems. Moreover, synthetic methodologies focused on improvements in terms of product yield, reaction duration, use of environmentally benign conditions and simplified workup procedures predominate among the recently developed approaches. Solid‐phase organic synthesis received considerable attention with the pioneering findings of Merrifield's solid‐phase peptide synthesis in 1963. A diverse range of organic, inorganic and organic‐inorganic substances have been utilized as polymeric solid supports in various catalytic applications. The recyclability and reusability of the immobilized catalysts over consecutive cycles establish them as an attractive alternative over conventional catalytic systems from the environment as well as industrial perspective. The present review summarizes the recent developments in the environmentally benign synthesis of benzothiazole derivatives using supported reagents. Different solid supports along with their catalytic application, mechanistic perspective and substrate tolerance have been discussed comprehensively. Abstract : Benzothiazole and its derivatives have been manifested as an optimistic scaffold due to their immense biological importance. Several protocols were discussed showing the power of utilizing both organic and inorganic polymeric skeleton as solid support. Milder reaction conditions, simpler work‐up procedures, superior yield and decreased reaction times and recycling capability of the supported reagent are some of the benefits of these protocols.